Development and evaluation of thermal and chemical microalgae cell disruption methods for biofuels and bioproducts production (Revista de Investigaciones Universidad del Quindío, 2015)
Biomass of microalgae continues under study as promising candidate for novel biofuels and bioproducts, however, microalgae-based processes faces technical bottlenecks related to efficiency of metabolite  extraction and transformation. This paper shows the development and evaluation of thermal and chemical cell disruption methods for the extraction of oil from  Nannochloropsis  sp.  as  feedstock  for the  production of third generation biofuels and high value fatty acids, in order to achieve lipid extraction efficiency. The thermal cell disruption process chosen was autoclave, during operation times of 1 and 3 hours at 394.15 K and 103410 Pa. Chemical treatment was  based on acid  hydrolysis with  HCl in concentrations  of  0.1,  0.5, 1  and 3 mol L-1. Organosolv Pretreatment was also used with a reaction time of 4.1 hours at 394.15 K and  103410  Pa. Results showed that the thermal and Organosolv cell disruption process increases extraction yields for biomass without pretreatment, but these did not exceed any of the results obtained with acid hydrolysis. Solution 0.5 mol L-1 HCl proved to be the most suitable for cell disruption process.  In  addition it was determined that the water content in the pretreated biomass, decreases the efficiency of the extraction processes.
Keywords: Microalgae; cell disruption; extraction; lipid extracts